Culture medium for amylase production by toxigenic fungi - Figueira,Edson Luiz Zangrando (2000)
Mycelial growth and amylase production by a mycotoxigenic strain of Fusarium moniliforme and Aspergillus flavus were evaluated in a culture medium containing starch, glycerol, wheat bran or corn. With emphasis on corn, different fractions composed by germ, degermed seed, starch, milky stage corn and the respective starch or supernatant fraction were analyzed for F. moniliforme growth . The medium composed of milky stage corn supernatant promoted the best mycelial growth (p<0.05), and it was used to prepare amylase production medium in the next step. The medium composed with 2% ground corn in milky stage corn supernatant (350g of milky stage corn blended with 250mL water and centrifuged) promoted the highest amylase production, which was at the 10th day of fermentation, both for F. moniliforme (42.32U/mL) and A. flavus (4,745.54U/mL).